Status of Cassava (Manihot Esculenta Crantz) in Côte d’Ivoire: From Production to Consumption and Evaluation of Technology Adoption - Modeste, Kouassi Kan; Adolphe, Mahyao; Boni, N’zue; Edmond, Koffi; Camille, Koffi (European Scientific Journal, ESJ, 2018)
The current state of cassava production and technology level as well as commercialization and consumption aspects were studied in Côte d’Ivoire. The study involved a sample of 570 actors of the value chain randomly selected in three (3) agro ecological regions (south, west and centre). Using a baseline survey questionnaire, 150 producers, 195 transformers and 195 consumers were interviewed. Results showed that farmers and consumers households are in majority led by men (80 and 61%) while transformers households are led by women (81%). Concerning the level of adoption of cassava technologies, it was found that about 35% of cassava growers are aware about the new cassava varieties and more than 80% agreed to use them. The analysis performed in agro ecological regions revealed that traditional varieties are preferred (40 % to 90 %) to improved varieties. Improved varieties, Bocou 1 (10.67%), TMS4 (2)1425 (0.67%) and Bocou 2 (0.67%) are less preferred for cultivation in spite of high yields, food processing or taste qualities, respectively mentioned by farmers. More than 50 % of farmers agreed to adopt the Rapid Seed Multiplication technique. Contrary to the localities of Man (West) and Bonoua (South) where pounded cassava is more consumed (89.29% and 66%), dehydrated cassava (Attieke) food is the most consumed in other localities surveyed. In spite of the high yield of improved varieties and the desire of cassava growers to adopt new cassava technologies, research and extension services should be reinforced taking into account agro ecological specificities of production, commercialization and consumption.